UPAYA PENINGKATAN PENGEMBANGAN APARATUR PEMERINTAH DI KANTOR CAMAT - Kaja, Kaja (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
The improvement and development of apparatus resources are carried out through education and training, such as in the field of administration, which includes education in archiving and letter writing. In the field of government, it includes making letters and determining letter numbers related to sub-district government, as well as financial management, such as general cash books, auxiliary cash books for receipts, and expenditure cash books. Additionally, in the field of community affairs, it includes procedures for making population reports, population data collection, and making letters such as certificates of obtaining identity cards, family cards, birth certificates, and certificates of economic inability (poverty). Besides government training, there are also training for civil servants and promotion training. With education and training, it can add experience and skills or expertise in carrying out tasks, thereby increasing efficiency and reducing costs. This study aims to describe and illustrate the improvement and development of apparatus through education and training, as well as motivation and coaching for employees. This type of research uses qualitative descriptive research, which describes the actual situation in the field, while the research subjects are the Head of Sub-district and the Head of Employee Development Section. Data collection tools used are interview guidelines, observation, and documentation. Based on the research findings, it can be concluded that the development of apparatus resources has been carried out through training and education, as well as good coaching and work motivation. The suggestion that can be proposed is that education and training, motivation, and coaching should be carried out continuously and maintained.